Titanium-based lead dioxide electrode with micro-nano structure and preparation method thereof

By performing nanosecond laser processing on the titanium plate and forming a tin antimony oxide intermediate layer, and combining with the electrodeposition method, titanium-based lead dioxide electrode with micro-nano structure was prepared, which solved the problem of insufficient stability and corrosion resistance of the traditional electrodes, and significantly improved the electrocatalytic performance and service life.

CN119913554APending Publication Date: 2025-05-02JILIN UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510032414.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The traditional titanium-based lead dioxide electrode has problems such as large grain size of the active layer, loose crystal arrangement, poor stability and corrosion resistance, easy shedding and short service life, resulting in poor electrocatalytic performance.

Method used

High-precision processing on the titanium plate by nanosecond laser was performed to form a titanium matrix with a periodic microarray structure, and a dense tin antimony oxide intermediate layer was formed thereon. Lead dioxide was uniformly deposited by electrodeposition method to prepare a titanium-based lead dioxide electrode with a micro-nano structure.

Benefits of technology

It improves the specific surface area of ​​the electrode, provides more active sites, enhances electrocatalytic performance and stability, and extends the service life of the electrode. At the same time, the process is simple, environmentally friendly, low energy consumption and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913554A_ABST
    Figure CN119913554A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-based lead dioxide electrode with a micro-nano structure and a preparation method of the titanium-based lead dioxide electrode. The method comprises the following steps: firstly, carrying out fine processing on a smooth titanium plate by adopting nanosecond laser to construct a surface microarray structure, then, forming a compact tin-antimony oxide intermediate layer on the processed titanium plate by adopting a thermal deposition method, and finally, carrying out deposition of lead dioxide on a titanium substrate by adopting an electro-deposition method. The prepared electrode has a relatively large specific surface area, can provide more active sites, and has good electro-catalytic performance, stability and relatively long service life. According to the preparation method, laser etching and electro-deposition are combined, and the preparation method has the advantages of being easy and convenient to operate, green, safe, low in energy consumption, low in cost and the like and has certain industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode material preparation, and in particular to a titanium-based lead dioxide electrode with a micro-nano structure and a preparation method thereof. Background Art

[0002] In electrocatalytic oxidation reactions, the conversion efficiency of reactants is greatly affected by the anode material, so it is necessary to design and develop an efficient anode material. Titanium-based lead dioxide electrode is considered to be an anode material with good corrosion resistance and high oxygen evolution overpotential due to its good conductivity, high stability, simple preparation and low cost. However, traditional PbO2 electrodes usually face problems such as large active layer grain size, loose crystal arrangement, poor stability and corrosion resistance, easy detachment from the substrate and short service life. In addition, the low specific surface area of ​​the electroplated PbO2 film limits the number of active sites on the surface of the PbO2 electrode, resulting in low current efficiency and poor electrocatalytic performance of the PbO2 electrode, which restricts its practical application.

[0003] The current strategies for improving PbO2 electrodes mainly include the following three aspects: (1) optimizing the intermediate layer to enhance the adhesion between the deposited layer and the substrate, improving the electrode stability and extending the service life; (2) developing new preparation methods to make the active layer have a high specific surface area, thereby improving the catalytic performance of the electrode; (3) doping metal and non-metal elements in the active layer to obtain high catalytic activity.

[0004] Among various methods for preparing lead dioxide electrodes, patent CN113755872B discloses a method for preparing a high-stability titanium-based lead dioxide electrode. This method uses a Ti substrate coated with a SnO2-Sb2O3 coating as the positive electrode, controls the temperature to 50~70°C in an acidic electrolyte containing Pb(NO3)2, NaF and polystyrene sulfonic acid, and uses a pulse current to obtain a Ti / PbO2 electrode. Patent application CN118600488A discloses a method for preparing a titanium-based lead dioxide electrode. This method uses a pretreated titanium substrate as an anode, a pure titanium plate as a cathode, and a lead methanesulfonate solution as an electroplating solution, and performs electrodeposition under heating conditions. Patent application CN116143248A discloses a method for preparing a lead dioxide electrode material for wastewater treatment. The method adds lead salt, copper salt, lead salt-soluble acid and fluoride salt to pure water with a conductivity of less than 15μs / cm to obtain an electrodeposition solution; immerses the cathode and anode substrates in the electrodeposition solution, and forms a lead dioxide active layer on the surface of the anode substrate by electrodeposition. Patent CN112093858B discloses a method for preparing a long-life lead dioxide electrode and its intelligent design. The method controls the temperature at 65°C in an electrodeposition solution containing Pb(NO3)2, NaF and HNO3, and prepares a lead dioxide electrode with a three-layer sandwich structure by constant current electrodeposition.

[0005] In the above patents, the lead dioxide electrode as an electrocatalytic anode still has deficiencies in catalytic activity and application. Summary of the invention

[0006] The present invention aims at the problems of the above-mentioned traditional lead dioxide electrodes in practical applications. It uses nanosecond laser to perform high-precision processing on titanium plates, adopts thermal deposition method to form a dense tin antimony oxide intermediate layer on the processed titanium plates, and uses electrodeposition method to uniformly deposit lead dioxide on the pretreated titanium substrate to prepare a titanium-based lead dioxide electrode with micro-nano structure. The prepared electrode has a large specific surface area, can provide more active sites, has good electrocatalytic performance, stability and long service life. The preparation method combines laser etching with electrodeposition, has the advantages of simple operation, green safety, low energy consumption and low cost, and has certain industrial application prospects.

[0007] The technical implementation scheme of the present invention is as follows: A titanium-based lead dioxide electrode with a micro-nano structure and a preparation method thereof, the specific steps are as follows: (1) Using nanosecond laser technology, laser etching is performed on a titanium plate or a titanium grid to obtain a titanium substrate A having a periodic microarray structure consisting of evenly spaced conical papillary structures and circular holes; the diameter of the conical papillary structures and circular holes in the periodic microarray structure of the titanium substrate A is 50 to 100 μm; (2) The titanium substrate A is ultrasonically cleaned in an alkaline solution and ultrapure water for 15 minutes respectively, then etched in hydrochloric acid, and then cleaned with ultrapure water to obtain a titanium substrate B, which is stored in ultrapure water or ethanol for later use; (3) SnCl2 and SbCl3 are dissolved in isopropanol at a molar ratio of 9:1 to obtain a coating solution, and a small amount of concentrated hydrochloric acid is added to prevent hydrolysis; the coating solution is brushed on the titanium substrate B, and then dried and pyrolyzed at 80-100°C and 450-500°C, respectively, and repeated for multiple times, and finally sintered at 450-500°C for one hour to form a dense layer of tin antimony oxide on the titanium substrate B to obtain substrate C (Ti / SnO2-Sb2O5); (4) preparing a mixed solution of lead nitrate, sodium fluoride, sodium citrate and nitric acid as an electrodeposition solution, using substrate C as an anode, platinum as a cathode, and an Ag / AgCl electrode as a reference electrode to perform electrodeposition to obtain a target electrode; In the electrodeposition solution, the concentration of lead nitrate is 0.4-0.6 mol / L, the concentration of sodium fluoride is 0.03-0.05 mol / L, the concentration of sodium citrate is 0.002-0.004 mol / L, and the concentration of nitric acid is 0.4-0.6 mol / L.

[0008] Preferably, the titanium plate in step (1) has a size of 1×1.5 cm, and the titanium grid has a size of 2×2 cm.

[0009] Preferably, the laser etching parameters in step (1) are as follows: scanning interval: 50-100 µm, output power: 15-25 W, scanning speed: 80-100 mm / s, repeated 5-8 times; the diameter of the conical papilla structure and the circular hole in the periodic microarray structure can be adjusted by changing the scanning interval.

[0010] Preferably, the alkaline solution in step (2) is a 10 wt % NaOH solution; Preferably, in step (2), the etching time in hydrochloric acid is 30 minutes, and the volume fraction of hydrochloric acid is 30%. Preferably, the brushing times in step (3) are 8 to 12 times, and the drying and pyrolysis times are both 5 minutes.

[0011] Preferably, the electrodeposition method in step (5) is a cyclic voltammetric deposition method with a voltage range of 1.7-2.5 V, a scan rate of 17-20 mV / s, and a deposition coulomb of 15-25 C cm -2 .

[0012] Beneficial effects of the present invention: (1) The target electrode surface deposited layer prepared by the present invention has a β-PbO2 crystal form, and its surface morphology is an elongated spindle shape with a significant micro-nano hierarchical structure, which increases the specific surface area of ​​the electrode and provides abundant active sites, thereby improving the electrocatalytic activity.

[0013] (2) The present invention introduces a tin-antimony intermediate layer between the titanium substrate and the lead dioxide deposition layer, thereby enhancing the bonding force between the two, thereby improving the stability of the electrode and extending the service life of the electrode.

[0014] (3) The method provided by the present invention combines laser etching with electrodeposition. No strong oxidant / reducing agent is added during the preparation process. The reaction is carried out at room temperature and pressure. The synthesis process has the advantages of simple operation, environmental friendliness, and wide applicability.

[0015] (4) The nanosecond laser technology used in the present invention can accurately control the etching morphology by controlling the moving path of the laser beam through a computer, and has the advantages of high speed, high precision, simple operation, and small heat-affected zone. The surface roughness and specific surface area of ​​the titanium substrate after laser etching are significantly increased, which enhances the bonding force between the substrate and the deposited layer, and also provides a basis for the surface morphology and micro-nano hierarchical structure of β-PbO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a SEM image of the titanium substrate after laser etching.

[0017] FIG. 2 is a low-magnification SEM image of a titanium-based lead dioxide electrode having a micro-nano hierarchical structure.

[0018] FIG. 3 is a high-magnification SEM image of a titanium-based lead dioxide electrode having a micro-nano hierarchical structure.

[0019] FIG. 4 is an XRD diagram of a titanium-based lead dioxide electrode having a micro-nano hierarchical structure. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below through examples, but the protection scope of the present invention is not limited to the scope of the examples.

[0021] Example 1 A titanium-based lead dioxide electrode with a micro-nano structure specifically comprises the following steps: (1) Preparation of titanium substrate: Nanosecond laser technology was used to perform high-precision micromachining on a titanium plate (1 cm × 2 cm) to obtain a titanium substrate A with a periodic microarray structure. The laser etching parameters were as follows: scanning interval of 50 µm, output power of 25 W, scanning speed of 80 mm / s, repeated etching 8 times, and etching area of ​​1 cm × 1.5 cm.

[0022] (2) Titanium substrate pretreatment: Titanium substrate A was ultrasonically cleaned in 10wt% NaOH solution and ultrapure water for 15 minutes, and then boiled in 30% hydrochloric acid for 30 minutes. Titanium substrate B was cleaned with ultrapure water and stored in ultrapure water or ethanol for later use.

[0023] (3) Preparation of tin-antimony intermediate layer: SnCl2 and SbCl3 were dissolved in isopropanol at a molar ratio of 9:1, and a small amount of concentrated hydrochloric acid was added to prevent hydrolysis. The coating liquid was brushed on the titanium substrate B, dried in an oven at 100°C for 5 minutes, and then thermally oxidized in a muffle furnace at 500°C for 5 minutes. The operation was repeated 12 times, and finally sintered at 500°C for 1 hour to form a dense layer of tin-antimony oxide on the titanium substrate B to obtain substrate C (Ti / SnO2-Sb2O5).

[0024] (4) Preparation of surface PbO2 active layer: Prepare a mixed solution containing 0.5 mol / L lead nitrate, 0.04 mol / L sodium fluoride, 0.002 mol / L sodium citrate and 0.5 mol / L nitric acid as the electrodeposition solution. Electrodeposition was performed with substrate C as the anode, platinum as the cathode, and Ag / AgCl electrode as the reference electrode. The voltage range was 1.7~2.5V, the scanning speed was 20mV / s, and the scanning cycle was 2 circles. After the electrodeposition was completed, the sample was washed with deionized water and dried to obtain the target electrode.

[0025] (5) The electrode obtained in Example 1 was characterized by SEM and XRD. The experimental results showed that the electrode had a good micro-nano hierarchical structure and the crystal form of the deposited layer was β-PbO2.

[0026] Example 2 A titanium-based lead dioxide electrode with a micro-nano structure specifically comprises the following steps: (1) Preparation of titanium substrate: Nanosecond laser technology was used to perform high-precision micromachining on a titanium plate (1 cm × 2 cm) to obtain a titanium substrate A with a periodic microarray structure. The laser etching parameters were as follows: scanning interval of 50 µm, output power of 25 W, scanning speed of 80 mm / s, repeated etching 8 times, and etching area of ​​1 cm × 1.5 cm.

[0027] (2) Titanium substrate pretreatment: Titanium substrate A was ultrasonically cleaned in 10wt% NaOH solution and ultrapure water for 15 minutes, and then boiled in 30% hydrochloric acid for 30 minutes. Titanium substrate B was cleaned with ultrapure water and stored in ultrapure water or ethanol for later use.

[0028] (3) Preparation of tin-antimony intermediate layer: SnCl2 and SbCl3 were dissolved in isopropanol at a molar ratio of 9:1, and a small amount of concentrated hydrochloric acid was added to prevent hydrolysis. The coating liquid was brushed on the titanium substrate B, dried in an oven at 100°C for 5 minutes, and then thermally oxidized in a muffle furnace at 500°C for 5 minutes. The operation was repeated 12 times, and finally sintered at 500°C for 1 hour to form a dense layer of tin-antimony oxide on the titanium substrate B to obtain substrate C (Ti / SnO2-Sb2O5).

[0029] (4) Preparation of surface PbO2 active layer: Prepare a mixed solution containing 0.5 mol / L lead nitrate, 0.04 mol / L sodium fluoride, 0.002 mol / L sodium citrate and 0.5 mol / L nitric acid as the electrodeposition solution. Electrodeposition was performed with substrate C as the anode, platinum as the cathode, and Ag / AgCl electrode as the reference electrode. The voltage range was 1.7~2.5V, the scanning speed was 17mV / s, and the cycle scan was 1 circle. After the electrodeposition was completed, the sample was washed with deionized water and dried to obtain the target electrode.

[0030] (5) The electrode obtained in Example 2 was characterized by SEM and XRD. The experimental results showed that the electrode had a good micro-nano hierarchical structure and the crystal form of the deposited layer was β-PbO2.

[0031] Example 3 A titanium-based lead dioxide electrode with a micro-nano structure specifically comprises the following steps: (1) Preparation of titanium substrate: Nanosecond laser technology was used to perform high-precision micromachining on a titanium grid (2 cm × 2 cm) to obtain a titanium substrate A with a periodic microarray structure. The laser etching parameters were as follows: scanning interval of 50 µm, output power of 25 W, scanning speed of 80 mm / s, repeated etching 8 times, and etching area of ​​2 cm × 2 cm.

[0032] (2) Titanium substrate pretreatment: Titanium substrate A was ultrasonically cleaned in 10wt% NaOH solution and ultrapure water for 15 minutes, and then boiled in 30% hydrochloric acid for 30 minutes. Titanium substrate B was cleaned with ultrapure water and stored in ultrapure water or ethanol for later use.

[0033] (3) Preparation of tin-antimony intermediate layer: SnCl2 and SbCl3 were dissolved in isopropanol at a molar ratio of 9:1, and a small amount of concentrated hydrochloric acid was added to prevent hydrolysis. The coating liquid was brushed on the titanium substrate B, dried in an oven at 100°C for 5 minutes, and then thermally oxidized in a muffle furnace at 500°C for 5 minutes. The operation was repeated 12 times, and finally sintered at 500°C for 1 hour to form a dense layer of tin-antimony oxide on the titanium substrate B to obtain substrate C (Ti / SnO2-Sb2O5).

[0034] (4) Preparation of surface PbO2 active layer: Prepare a mixed solution containing 0.5 mol / L lead nitrate, 0.04 mol / L sodium fluoride, 0.002 mol / L sodium citrate and 0.5 mol / L nitric acid as the electrodeposition solution. Electrodeposition was performed with substrate C as the anode, platinum as the cathode, and Ag / AgCl electrode as the reference electrode. The voltage range was 1.7~2.5V, the scanning speed was 20mV / s, and the scanning cycle was 5 times. After the electrodeposition was completed, the sample was washed with deionized water and dried to obtain the target electrode.

[0035] (5) The electrode obtained in Example 3 was characterized by SEM and XRD. The experimental results showed that the electrode had a good micro-nano hierarchical structure and the crystal form of the deposited layer was β-PbO2.

[0036] Example 4 A titanium-based lead dioxide electrode with a micro-nano structure specifically comprises the following steps: (1) Preparation of titanium substrate: Nanosecond laser technology was used to perform high-precision micromachining on a titanium grid (2 cm × 2 cm) to obtain a titanium substrate A with a periodic microarray structure. The laser etching parameters were as follows: scanning interval of 50 µm, output power of 25 W, scanning speed of 80 mm / s, repeated etching 8 times, and etching area of ​​2 cm × 2 cm.

[0037] (2) Titanium substrate pretreatment: Titanium substrate A was ultrasonically cleaned in 10wt% NaOH solution and ultrapure water for 15 minutes, and then boiled in 30% hydrochloric acid for 30 minutes. Titanium substrate B was cleaned with ultrapure water and stored in ultrapure water or ethanol for later use.

[0038] (3) Preparation of tin-antimony intermediate layer: SnCl2 and SbCl3 were dissolved in isopropanol at a molar ratio of 9:1, and a small amount of concentrated hydrochloric acid was added to prevent hydrolysis. The coating liquid was brushed on the titanium substrate B, dried in an oven at 100°C for 5 minutes, and then thermally oxidized in a muffle furnace at 500°C for 5 minutes. The operation was repeated 12 times, and finally sintered at 500°C for 1 hour to form a dense layer of tin-antimony oxide on the titanium substrate B to obtain substrate C (Ti / SnO2-Sb2O5).

[0039] (4) Preparation of surface PbO2 active layer: Prepare a mixed solution containing 0.5 mol / L lead nitrate, 0.04 mol / L sodium fluoride, 0.002 mol / L sodium citrate and 0.5 mol / L nitric acid as the electrodeposition solution. Electrodeposition was performed with substrate C as the anode, platinum as the cathode, and Ag / AgCl electrode as the reference electrode. The voltage range was 1.7~2.5V, the scanning speed was 17mV / s, and the scanning cycle was 3 times. After the electrodeposition was completed, the sample was washed with deionized water and dried to obtain the target electrode.

[0040] (5) The electrode obtained in Example 4 was characterized by SEM and XRD. The experimental results showed that the electrode had a good micro-nano hierarchical structure and the crystal form of the deposited layer was β-PbO2.

[0041] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a titanium-based lead dioxide electrode with a micro-nano structure, characterized in that: The specific steps of this method are as follows: (1) Using nanosecond laser technology, laser etching is performed on a titanium plate or a titanium grid to obtain a titanium substrate A having a periodic microarray structure consisting of evenly spaced conical papillary structures and circular holes; the diameter of the conical papillary structures and circular holes in the periodic microarray structure of the titanium substrate A is 50 to 100 μm; (2) The titanium substrate A is ultrasonically cleaned in an alkaline solution and ultrapure water for 15 minutes respectively, then etched in hydrochloric acid, and then cleaned with ultrapure water to obtain a titanium substrate B, which is stored in ultrapure water or ethanol for later use; (3) SnCl2 and SbCl3 are dissolved in isopropanol at a molar ratio of 9:1 to obtain a coating solution, and a small amount of concentrated hydrochloric acid is added to prevent hydrolysis; the coating solution is brushed onto a titanium substrate B, and then dried and pyrolyzed at 80-100°C and 450-500°C, respectively, and repeated multiple times, and finally sintered at 450-500°C for one hour to form a dense layer of tin antimony oxide on the titanium substrate B to obtain a substrate C; (4) preparing a mixed solution of lead nitrate, sodium fluoride, sodium citrate and nitric acid as an electrodeposition solution, using substrate C as an anode, platinum as a cathode, and an Ag / AgCl electrode as a reference electrode to perform electrodeposition to obtain a target electrode; In the electrodeposition solution, the concentration of lead nitrate is 0.4-0.6 mol / L, the concentration of sodium fluoride is 0.03-0.05 mol / L, the concentration of sodium citrate is 0.002-0.004 mol / L, and the concentration of nitric acid is 0.4-0.6 mol / L.

2. The method for preparing a titanium-based lead dioxide electrode with a micro-nano structure according to claim 1, characterized in that: The size of the titanium plate described in step (1) is 1×1.5 cm, and the size of the titanium grid is 2×2 cm.

3. The method for preparing a titanium-based lead dioxide electrode with a micro-nano structure according to claim 1, characterized in that: The laser etching parameters in step (1) are as follows: scanning interval: 50~100µm, output power: 15~25W, scanning speed: 80~100mm / s, repeated 5~8 times.

4. The method for preparing a titanium-based lead dioxide electrode with a micro-nano structure according to claim 1, characterized in that: The alkaline solution in step (2) is a 10 wt % NaOH solution.

5. The method for preparing a titanium-based lead dioxide electrode with a micro-nano structure according to claim 1, characterized in that: In step (2), the etching time in hydrochloric acid is 30 minutes, and the volume fraction of hydrochloric acid is 30%.

6. The method for preparing a titanium-based lead dioxide electrode with a micro-nano structure according to claim 1, characterized in that: The number of times of brushing, drying and pyrolysis described in step (3) is 8 to 12 times.

7. The method for preparing a titanium-based lead dioxide electrode with a micro-nano structure according to claim 1, characterized in that: The drying and pyrolysis times in step (3) are both 5 minutes.

8. The method for preparing a titanium-based lead dioxide electrode with a micro-nano structure according to claim 1, characterized in that: The electrodeposition method described in step (5) is a cyclic voltammetric deposition method with a voltage range of 1.7-2.5 V, a scan rate of 17-20 mV / s, and a deposition coulomb of 15-25 C cm -2 .

9. A titanium-based lead dioxide electrode with a micro-nano structure prepared according to the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • A method for preparing a long-life lead dioxide electrode and its parameter design method

    CN112093858B

  • A method for preparing a highly stable titanium-based lead dioxide electrode

    CN113755872B

  • Preparation method of lead dioxide electrode material for wastewater treatment

    CN116143248A

  • Preparation method of titanium-based lead dioxide electrode

    CN118600488A

  • Composite wear-resistant antifriction coating on titanium alloy surface and preparation method thereof

    CN104480511A